Difficulties faced by physicians from four European countries in rebutting antivaccination arguments: a cross-sectional study - Fernanda Rodrigues; Cornelia Betsch; Pierre Verger; Harriet Fisher; Philipp Schmid; Dawn Holford; Angelo Fasce; Amanda Garrison; Linda Karlsson; Frederike Taubert; Stephan Lewandowsky; Anna Soveri (BMJ Public Health)
Introduction Physicians play a critical role in encouraging their patients to get vaccinated, in part by responding to patients’ concerns about vaccines. It is, therefore, important to understand what difficulties physicians have in dealing with different concerns they may encounter. The aim of this article was to determine physicians’ perceptions of difficulties in rebutting different antivaccination arguments from patients using data collected as part of a cross-sectional, cross-national questionnaire on physicians’ vaccine attitudes and behaviours.Methods Physicians in 4 European countries (Finland, Germany, France and Portugal, total n=2718) rated 33 different arguments, chosen to represent 11 different psychological motivations underlying vaccine hesitancy, in terms of their perceptions of how difficult each argument would be to rebut.Results Across all countries, physicians perceived arguments based on religious concerns and ‘reactance’ (ie, resistance to perceived curbs of freedom) to be the most difficult to rebut, whereas arguments based on patients’ distorted perception of the risks of disease and vaccines were perceived to be the easiest. There were also between-country differences in the level of perceived difficulty of argument rebuttal. Physicians’ perceived difficulty with rebutting arguments was significantly negatively correlated with their vaccine recommendation behaviours and their preparedness for vaccination discussions.Conclusions Physicians may feel better equipped to counter arguments that can be rebutted with facts and evidence but may struggle to respond when arguments are motivated by psychological dispositions or values.